2019
DOI: 10.3389/fimmu.2019.01183
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Plasma Cells Modulate Local Myeloid-Lineage Differentiation via IL-10

Abstract: Bone marrow plasma cells have been reported to represent a major source of IL-10; however, the impact of plasma cell derived IL-10 in that tissue remains poorly understood. We confirm in this study that even in the absence of acute immune reactions, mature plasma cells represent the dominant IL-10+ cell population in the bone marrow, and identify myeloid-lineage cells as a main local target for plasma cell derived IL-10. Using Vert-X IL-10 transcriptional reporter mice, we found that more than 50% of all IL-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…These data lend strong support to a model where LLPCs generated from acute immunizations destined for bone marrow niches can survive in peripheral sites and secrete antigen-specific antibodies for extended periods of time (117). Hence, PC localization in bone marrow niches may play other roles that are independent of antibody secretion (118,119).…”
Section: Plasma Cell Nichessupporting
confidence: 62%
“…These data lend strong support to a model where LLPCs generated from acute immunizations destined for bone marrow niches can survive in peripheral sites and secrete antigen-specific antibodies for extended periods of time (117). Hence, PC localization in bone marrow niches may play other roles that are independent of antibody secretion (118,119).…”
Section: Plasma Cell Nichessupporting
confidence: 62%
“…Recently, two studies reported that PC accumulation with age regulates the production of inflammatory factors by BM stromal cells, which in turn promotes myeloid-biased HSCs (144,145). This impact on myeloid cells is probably due to the ability of PCs to produce IL-10, one of the key drivers of the myeloid differentiation (145,146). Consequently, both studies suggest a potential impact of PCs on MSCs and on the skewing of MPPs toward myeloid lineage with age (10).…”
Section: Concluding Remarks and Unanswered Questionsmentioning
confidence: 99%
“…It is known that both myelopoiesis and the number of PCs increase with aging in the BM. Recently, two studies reported that PC accumulation with age regulates the production of inflammatory factors by BM stromal cells, which in turn promotes myeloid-biased HSCs (144,145). This impact on myeloid cells is probably due to the ability of PCs to produce IL-10, one of the key drivers of the myeloid differentiation (145,146).…”
Section: Concluding Remarks and Unanswered Questionsmentioning
confidence: 99%
“…Pharmacological blockade of IL-1 and tumor necrosis factor-alpha (TNF-α) signaling reduced granulopoiesis in aged mice demonstrating the importance of these factors in the age-associated increase in myelopoietic output (17). Notably, a recently published study (16) demonstrated that in vitro derived mouse PCs had the potential to regulate the composition of myeloid cells generated in culture. Here, IL-10 was the critical regulator that skewed the myeloid compartment toward a more macrophage-like cell fate (16).…”
Section: More Than Just Antibody Factoriesmentioning
confidence: 99%
“…Notably, a recently published study (16) demonstrated that in vitro derived mouse PCs had the potential to regulate the composition of myeloid cells generated in culture. Here, IL-10 was the critical regulator that skewed the myeloid compartment toward a more macrophage-like cell fate (16).…”
Section: More Than Just Antibody Factoriesmentioning
confidence: 99%